(untitled) - Wackernagel, Mathis (Gabriola Island, 1996)
Contents: Ecological footprint for beginners; footprints and sustainability; fun with footprints methods; the search for sustainbility strategies; avoiding overshoot.
Keywords: Sustainable development,Human ecology